Use of mirror therapy to treat psychogenic tremors - Duymaz, Tomris (European Journal of Therapeutics, 2018)
ABSTRACT: Psychogenic tremors present with various clinical demonstrations in neurological practice. In mirror therapy, the patient concentrates on the image of the normal limb and learns to manage pain and movement. This study aimed to use mirror therapy for the treatment of psychogenic tremors. A 19-year-old female presented in the hospital with complaints of incompetence in manual skills, sluggish movements, reduction in muscle strength, weakness of fine motor activities, and presence of involuntary movements, such as tremors in the right upper extremity, which appeared approximately 2 years ago but worsened in the last 1 year. Both before and after treatment, we used a digital goniometer to assess the range of motion of the forearm and wrist, digital hand-held dynamometer to evaluate flexor and extensor muscles of the hand and wrist, hand grip dynamometer and pinchmeter to evaluate muscle strength, Disabilities of the Arm, Shoulder and Hand (DASH)questionnaire to assess the functional capacity of the upper extremity, Jebsen hand function test to evaluate the functionality of the hand, Grooved Pegboard test to evaluate manipulative skills, and functional independence measure (WeeFIM) to evaluate the quality of life. There was an improvement in all the parameters when compared before and after treatment. The results of this study showed that mirror therapy was a very useful approach in the treatment of psychogenic tremors, which significantly disrupt exercise compliance and are characterized by severe psychogenic tremors that reduce the quality of life.
Keywords: Mirror therapy; psychogenic; tremor